PENGGUNAAN METODE BERNYANYI DALAM MENINGKATKAN MUFRADAT BAHASA ARAB SISWA KELAS I MI YA BAKII KESUGIHAN 01 - Miladia Nur Khasanah; Lumaurridlo (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2024)
Kurt Lewin's Classroom Action Research (PTK) model was used in this research, which aims to improve mastery of Arabic mufradat in class I MI Ya BAKII Kesugihan 01 Kesugihan District, Cilacap Regency through singing. Based on observations of teacher activities, the results of data analysis showed that cycle I activity was 84.61 (good), while cycle II activity was 92.30 (very good). The results of observation of student activities in cycle I reached 69.23 (satisfactory), while cycle II experienced an increase to 85.89 (satisfactory). Teachers have not used the singing method to teach Arabic to students at the pre-cycle stage, so the percentage of students' mastery of mufradat is 25.80%, very low, and the class average is 59.77, lower. The teacher uses singing to teach Arabic mufradat in cycle I. The peak level of student learning in cycle I was 51.6% (low) with a normal class score of 67.70 (sufficient), while in cycle II the level of student learning fulfillment increased. to 90.3% (great) with a typical score - normal class of 80.77 (great). So it can be concluded that the application of the singing method for class I C MI Ya BAKII Kesugihan 01 students on the material أسماء الفواكه (names of fruit) has increased from initially 25.80% in the pre-cycle, after applying the singing method it increased to 90.3% with complete category.